Nieskończoność Boga u Orygenesa: przyczyna wielkiego nieporozumienia - Mrugalski, Damian (Vox Patrum, 2018)
Many historians of ideas – philosophers and theologians – believe that the first thinker to introduce the concept of a positive understanding of the infiniteness of God was Plotinus. In Greek philosophy, however, something infinite was understood as “unfinished” and therefore “imperfect”. All the same, according to many scholars, Christianity took the concept of the infiniteness of God precisely from the founder of neo-Platonism. One of the reasons for which researchers of the doctrines of the ancient world persist in this thesis even today is the fact that, in the writings of Origen – who lived at the time of Plotinus – we find the expressions which might give readers the impression that God’s power is finite, since God brought into existence a finite number of created beings. This article argues that this widely-held interpretation is wrong. Philo and Clement, a Jewish and a Christian thinker, both of Alexandria – from whose doctrines Origen borrowed abundantly – wrote of an infinite God before Origen did. In the surviving works of Origen, moreover, he nowhere states explicitly that God’s power is finite, although it is true that, according to him, God created a finite number of creatures. The controversial thesis of a finite God is found only in fragments written by ancient critics of Origen’s teaching. A detailed analysis of Origen’s own original pronouncements on the nature, power and knowledge of God leads one to the conclusion that the fragments that have led many historians of ideas into confusion, either do not represent the views of Origen himself or present Origen’s teachings inaccurately. Moreover, in Origen’s surviving Greek writings, we find the term ¥peiron used in reference to God. This is precisely the term used by Greek philosophers to designate infinity. We may posit, then, that the concept of the infiniteness of God, positively understood, was born of the encounter of Greek philosophy with the Bible – that is, with the Jewish and Christian doctrines of the first centuries of the common era. Origen, who came slightly later, continued the thought of his predecessors and does not contradict them anywhere in his surviving works. What remains to be examined is the question of whether Plotinus himself made use of the work of Jewish and Christian thinkers in forming his doctrine of an infinite God, rather than those thinkers leaning on Plotinus, as is usually assumed.